Dysregulation of Leukocyte Trafficking in Type 2 Diabetes: Mechanisms and Potential Therapeutic Avenues - Pezhman, Laleh; Tahrani, Abd; Chimen, Myriam (Frontiers in Cell and Developmental Biology, 2021)
Type 2 Diabetes Mellitus (T2DM) is a chronic inflammatory disorder that is characterized by chronic hyperglycemia and impaired insulin signaling which in addition to be caused by common metabolic dysregulations, have also been associated to changes in various immune cell number, function and activation phenotype. Obesity plays a central role in the development of T2DM. The inflammation originating from obese adipose tissue develops systemically and contributes to insulin resistance, beta cell dysfunction and hyperglycemia. Hyperglycemia can also contribute to chronic, low-grade inflammation resulting in compromised immune function. In this review, we explore how the trafficking of innate and adaptive immune cells under inflammatory condition is dysregulated in T2DM. We particularly highlight the obesity-related accumulation of leukocytes in the adipose tissue leading to insulin resistance and beta-cell dysfunction and resulting in hyperglycemia and consequent changes of adhesion and migratory behavior of leukocytes in different vascular beds. Thus, here we discuss how potential therapeutic targeting of leukocyte trafficking could be an efficient way to control inflammation as well as diabetes and its vascular complications.